Les francophones de l'Ontario de 65 ans et plus : un profil statistique - Cardinal, Linda; Plante, Nathalie; Sauvé, Anik (Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa, 2006)
fs-ref-orig: Cardinal, L., Plante, N. et Sauvé, A. (2006). Les francophones de l'Ontario de 65 ans et plus : un profil statistique. Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa. fs-code-orig: Cardinal-2006

Community involvement of seniors in the Eastern Townships - Gosselin, Chedly; Viens, Caroline (Journal of Eastern Townships Studies, 2006)
This paper explores Anglophone seniors' participation within the community of the Estrie region of Quebec. A healthy relationship between Anglophone and Francophone communities improves access to state health and social services and relieves the social isolation of those living in rural areas. Immigrant migration to the area as well as out-migration of young Anglophones is profoundly affecting the delivery of health and social services as well as changing family, community, nation, culture and what it means to be a citizen.

Les femmes aidantes naturelles dans les communautés francophones et acadienne du Canada. Sommaire - Ouimette, Johanne; Miron, Isabelle. N (Alliance des femmes de la francophonie canadienne, 2006)